ANALISIS PESERTA DIDIK YANG TERISOLIR DALAM KELOMPOK BELAJAR SISWA SMP NEGERI 8 PONTIANAK TAHUN 2020 - Ayu Rizkia Sapitri; Luhur Wicaksono; Yuline Yuline (Universitas Tanjungpura, 2022)
AbstractThis study aims to determine the characteristics of students who experience isolation, the factors that cause students to be isolated, the impact that occurs on isolated students and the efforts that have been made by Guidance and Counseling teachers for isolated students in the study group of SMP Negeri 8 Pontianak. The method used in this research is descriptive method, qualitative approach, collecting technique used is interview, documentation, sociometry and the research form is survey research. The subjects in this study were five students and their close friends and one Guidance and Counseling teacher. From the results of data analysis that has been carried out, the characteristics of isolated students are the lack of maturity in emotional control, selfconfidence and wisdom. The internal factors of isolated students are unable to adjust, quiet, closed. External factors are ignored from the group. The assistance provided by the Guidance and Counseling teacher in dealing with this isolated case is the provision of classical services, individual counseling, group guidance and group counseling.Keywords: Characteristics, Factors, Isolated Impact, Students